PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK KELAS V UPTD SD NEGERI 11 PAREPARE - Zaenal Susanto; Abdul Hakim; Naufal Qadri Syarif (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to describe how the Make A Match learning model is implemented, while also evaluating the increase in learning engagement among fifth-grade students at UPTD SD Negeri 11 Parepare regarding the